Collecting beetles on Leyte Island, Philippines - Schawaller, Wolfgang; Trautner, Juergen (Annals of Tropical Research, 1994)
Beetles belonging to 67 families were collected during a 3-week survey on coleoptera inhabiting forest floor, aquatic and semi-aquatic habitats, and lower stratum vegetation in the island of Leyte, Philippines. Highest number of species was found in the primary forests around Mount Pangasugan.